Developing a cultural-based realistic mathematics education learning video on congruence and similarity - Mahmudah, Faisa Nirbita; Rusmining, Rusmining (Universitas Ahmad Dahlan, 2022)
The Covid-19 pandemic has made learning activities carried out online so that many students have difficulty understanding the material, so interesting learning media are needed with flexible access. This study aims to develop a learning video with a culture-based RME approach on congruence and similarity materials and to determine the validity and practicality of the product. This type of research is development research with the ADDIE research model. The subjects of this study were students of class IX A MTs Negeri 9 Bantul. The data collection methods are interviews and questionnaires. The data analysis step is carried out by calculating and analyzing the results of the validity and practicality tests. The results of the product validity test obtained very valid criteria with an average value of 4.75 by material experts and 4.82 by media experts. At the same time, the practicality test got a percentage of 91.82% with very practical criteria in small class trials and a percentage of 82.67% with very practical criteria in large class trials. Based on these results, the learning video can be declared very valid and very practical to use in learning.